Clinical manifestations of Rathke's cleft cysts and their natural progression during 2 years in children and adolescents - Jo Eun Jung; Juhyun Jin; Mo Kyung Jung; Ahreum Kwon; Hyun Wook Chae; Duk Hee Kim; Ho-Seong Kim (Korean Society of Pediatric Endocrinology, 2017)
Purpose Rathke's cleft cyst (RCC) is an asymptomatic benign lesion. With increased interest in pediatric endocrinology, the prevalence of RCCs in children is also increasing. However, the clinical relevance and proper management of RCC is not well defined in children. Therefore, we investigated the clinical manifestations and radiologic features of RCC in children and adolescents, as well as the natural progression of RCC. Methods We retrospectively reviewed the medical records of 91 children and adolescents with RCC diagnosed with magnetic resonance imaging (MRI) in Severance Children's Hospital from January 2006 to December 2015. The clinical, hormonal, and imaging findings were analyzed in patient groups classified according to age. The size of each cyst was assessed in sixty patients who underwent follow-up MRI during the 2 years. Results Female patients were predominant (64 vs. 27). The common clinical features at presentation were endocrine dysfunction (59.3%), headache (23.0%), and dizziness (4.4%). Symptoms related to endocrine disorders were more frequent in younger patients. In 7 patients managed surgically, the cysts were significantly larger and more frequently located in the suprasellar region. Of 60 nonsurgical patients with a follow-up MRI performed within 2 years after the diagnosis, the RCC size increased in about 26.7% (n=16). Conclusions Although 94.4% of the patients with RCC had clinical symptoms, surgery was performed in only about 7.5% of patients. RCC is associated with pituitary insufficiency, thus, baseline and follow-up endocrine function tests are required. Additionally, regular MRI follow-up is required in long-term period to monitor change in size.